2013
DOI: 10.1007/s00449-013-0884-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of naphthalene metabolism by white rot fungus Pleurotus eryngii

Abstract: The use of biomaterials or microorganisms in PAHs degradation had presented an eye-catching performance. Pleurotus eryngii is a white rot fungus, which is easily isolated from the decayed woods in the tropical rain forest, used to determine the capability to utilize naphthalene, a two-ring polycyclic aromatic hydrocarbon as source of carbon and energy. In the meantime, biotransformation of naphthalene to intermediates and other by-products during degradation was investigated in this study. Pleurotus eryngii ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…The fungus Pleurotus eryngii F032 has been extensively investigated for its application in the degradation of naphthalene, a two-ring aromatic compound (Hadibarata et al 2013). Laccase has the powerful mechanism to degrade phenolic and non-phenolic compounds, while the secretion of lignin peroxidase (LiP) by fungi will enhance the decolorization of dye (Hadibarata et al 2012a, b;Hazeroual et al 2006).…”
mentioning
confidence: 99%
“…The fungus Pleurotus eryngii F032 has been extensively investigated for its application in the degradation of naphthalene, a two-ring aromatic compound (Hadibarata et al 2013). Laccase has the powerful mechanism to degrade phenolic and non-phenolic compounds, while the secretion of lignin peroxidase (LiP) by fungi will enhance the decolorization of dye (Hadibarata et al 2012a, b;Hazeroual et al 2006).…”
mentioning
confidence: 99%
“…Published findings have evaluated the effect of white-rot fungi on removal of gaseous chlorobenzene and naphthalene, while no reports have been published regarding this degradation using brown-rot fungi. Therefore, our next experiment would determine the ability of gaseous chlorobenzene or naphthalene in P. betulinus [36][37][38]. The findings of Krueger et al [38] indicated that brown-rot fungus Gloeophyllum trabeum might be suitable for the biodegradation of styrene.…”
Section: Discussionmentioning
confidence: 97%
“…The strain P. eryngii F032 was isolated from decayed woods in Indonesia's tropical rain forest. Isolation, identification, and culture media are described elsewhere .…”
Section: Methodsmentioning
confidence: 99%
“…Batch growth experiments of P. eryngii F032 were performed in 100‐mL conical flasks containing 20 mL of modified mineral salt broth medium (MSB) supplemented with three agar plugs (5 mm in diameter) and a substrate solution . The substrate solution consisted of fluoranthene (5 mg/L), dimethylformamide, and chloramphenicol to prevent the growth of bacteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation